A Biologically-Inspired Appearance Model for Snake Skin - Padron Griffe, Juan Raul; Bielsa, Diego; Jarabo, Adrian; Muñoz, Adolfo (Jornada de Jóvenes Investigadores del I3A, 2023)
We present a multilayered appearance model for snake skin, inspired on its anatomy: The top layer is a thin film layer producing a specular iridescent reflection, while the bottom layer is a diffuse highly-absorbing layer, that results into a dark diffuse appearance that maximizes the iridescent color of the skin.